1997
DOI: 10.1128/jb.179.21.6862-6864.1997
|View full text |Cite
|
Sign up to set email alerts
|

SigmaE is an essential sigma factor in Escherichia coli

Abstract: E is an alternative sigma factor that controls the extracytoplasmic stress response in Escherichia coli. E is essential at high temperatures but was previously thought to be nonessential at temperatures below 37°C. We present evidence that E is an essential sigma factor at all temperatures. Cells lacking E are able to grow at low temperatures because of the presence of a frequently arising, unlinked suppressor mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
182
1
5

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(191 citation statements)
references
References 17 publications
(32 reference statements)
3
182
1
5
Order By: Relevance
“…These include the heat-shock factor RpoH and stationary-phase protein RpoS of Escherichia coli (Morita et al, 1999;Weber et al, 2005), the general stress-response protein SigB of Bacillus subtilis (Peterson et al, 2001;Price et al, 2001;Price, 2002) and ECF (extracytoplasmic function) sigmas such as SigE of Streptomyces coelicolor, RpoE of E. coli and SigW of B. subtilis (Lonetto et al, 1994;Raina et al, 1995;Rouviere et al, 1995;De La Penas et al, 1997;Wiegert et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…These include the heat-shock factor RpoH and stationary-phase protein RpoS of Escherichia coli (Morita et al, 1999;Weber et al, 2005), the general stress-response protein SigB of Bacillus subtilis (Peterson et al, 2001;Price et al, 2001;Price, 2002) and ECF (extracytoplasmic function) sigmas such as SigE of Streptomyces coelicolor, RpoE of E. coli and SigW of B. subtilis (Lonetto et al, 1994;Raina et al, 1995;Rouviere et al, 1995;De La Penas et al, 1997;Wiegert et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…Envelope integrity is required under all growth conditions, and E is an essential transcription factor (De Las Penas et al 1997a). Perturbations in the integrity and protein-folding state of the envelope caused by temperature upshift, chaperone depletion, or accumulation of unassembled porins increase E activity; conversely, temperature downshift and/or depletion of porins decrease E activity (Mecsas et al 1993;Hiratsu et al 1995;Raina et al 1995;Rouviere et al 1995;Missiakas et al 1996;Rouviere and Gross 1996;Ades et al 2003).…”
mentioning
confidence: 99%
“…Interestingly, the three-dimensional structure of RseB revealed that it is composed of two domains; a small C-terminal domain that interacts with RseA and a large N-terminal domain (of unknown function), which shares structural similarity with the lipid binding proteins LolA, LolB, and LppX and, hence, is proposed to bind to a lipophilic molecule (e.g., a lipid, lipoprotein or LPS) that accumulates under stress (56,57). This binding to the N-terminal domain of RseB is believed to trigger its dissociation from RseA, thereby relieving the inhibition of the signal transduction pathway (46,55,56). Indeed Gross and coworkers (55) recently showed that ''maximal'' activation of SigmaE not only required the obligatory activation of DegS but also involved the derepression of RseB-mediated inhibition although to date the putative lipophilic molecule responsible for RseB derepression remains unknown.…”
Section: Proteolytic Control Of the Envelope Stress Response In E Colimentioning
confidence: 99%
“…So how is the unfolded protein stress signal sensed and transmitted across the membrane? In the absence of stress, SigmaE is bound, with high affinity, to the cytoplasmic domain of the anti-sigma factor, regulator of SigmaE (RseA) thereby inhibiting its transcriptional activity (44)(45)(46)(47) (Fig. 2a).…”
Section: Proteolytic Control Of the Envelope Stress Response In E Colimentioning
confidence: 99%
See 1 more Smart Citation